PENINGKATAN KEAHLIAN DESAIN BAGI PEMUDA KARANG TARUNA DALAM MENDUKUNG KEWIRAUSAHAAN - Setiyaningsih, Wiji (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The Youth Skill of Youth Lawang Village for Information Technology is still lacking, especially in the photoshop design side. There are no youth youths who have a background in multimedia school students, or who have worked on self-taught about photoshop design. Undoubtedly contrary to the current trend of community needs. There is a desire from some youth entrepreneurship developers in the multimedia field to take a short course on Photoshop design but have constrained by costs. The Head of Lawang Village hopes, the existing entrepreneurship has been increasing, to accommodate positive, creative activities contained in entrepreneurship, as well as training to work independently and improve the economy of the Lawang Village community. Based on the problems above, they are training to enhance Photoshop design skills for the youth of Lawang Village Youth Organization in supporting their entrepreneurship. The results of the training based on the percentage of pre-test and post-test photoshop design skills for youth Lawang Village increased by 98%. The proven that community service activities through this Photoshop design training activity were successful, and it was proven that after the training began ordering cartoon and wallpaper theme design stickers.